1990
DOI: 10.1530/jrf.0.0880569
|View full text |Cite
|
Sign up to set email alerts
|

Resumption of follicular activity in the early post-partum period of dairy cows

Abstract: Summary. Lactating Friesian dairy cows (2nd\p=n-\4thparity) which calved in spring (N = 7) or autumn (N = 15) were used. Their ovaries were examined by ultrasound scanning and blood samples were obtained daily for progesterone and oestradiol concentrations from the 5th day after calving until the first post-partum ovulation occurred. Five autumn-calving cows selected at random were bled every 15 min over a 6-h period on 1 day each week for 4 weeks after calving to assess the patterns of LH secretion. Follicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
122
0
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(140 citation statements)
references
References 14 publications
13
122
0
5
Order By: Relevance
“…This continued growth appears to be owing to lack of positive feedback induced by oestradiol and thus failure of induction of the LH/FSH pre-ovulatory surge, despite increased LH pulse frequency (to an intermediate level). At this time, systemic concentrations of progesterone are low, whereas concentrations of oestradiol are elevated above normal pro-oestrus concentrations (Savio et al, 1990b;Hatler et al 2003), resulting in many cases in strong exhibition of oestrous behaviour by cows in the early phases of a follicular cyst. This is followed by a period of time when there is an absence of oestrous behaviour in the second half of the cysts' lifespan.…”
Section: Follicular Cystsmentioning
confidence: 99%
See 1 more Smart Citation
“…This continued growth appears to be owing to lack of positive feedback induced by oestradiol and thus failure of induction of the LH/FSH pre-ovulatory surge, despite increased LH pulse frequency (to an intermediate level). At this time, systemic concentrations of progesterone are low, whereas concentrations of oestradiol are elevated above normal pro-oestrus concentrations (Savio et al, 1990b;Hatler et al 2003), resulting in many cases in strong exhibition of oestrous behaviour by cows in the early phases of a follicular cyst. This is followed by a period of time when there is an absence of oestrous behaviour in the second half of the cysts' lifespan.…”
Section: Follicular Cystsmentioning
confidence: 99%
“…With beef cows in good body condition, the first postpartum dominant follicle to ovulate is generally from wave 3.2 ± 0.2 (~30 days; Murphy et al, 1990), whereas for beef cows in poor body condition there are typically 10.6 ± 1.2 waves of follicular growth before ovulation occurs (~70 to 100 days; Stagg et al, 1995; Figure 3). In the case of dairy cows' ovulation of the first postpartum dominant follicle typically occurs in 30% to 80% of cows, whereas it undergoes atresia in 15% to 60% of cows or becomes cystic in 1% to 5% of cows (Savio et al, 1990b;Beam and Butler 1997;Sartori et al, 2004;Sakaguchi et al, 2004). There is no evidence that lack of FSH or a delayed resumption of ovarian follicle waves are causes of prolonged postpartum anoestrous intervals in either beef (Crowe et al, 1998;Stagg et al, 1998) or dairy cows (Beam and Butler, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there are three wave of ovarian follicular development occurring at about 7-day intervals in the bovine estrous cycle, and during the early postpartum period of a cow periodical follicular wave can also occur [1,7,8]. Since a long-term observation at a short interval, such as 3 days, would negatively influence the reproductive function of a cow, we introduced 7-day intervals in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Early resumption of ovarian activity is essential for timed cow conception, and thus for achieving an economically acceptable length of the open period. Crucial events in the resumption of ovarian activity postpartum (pp) are the emergence of the 1 st follicular wave (Lucy, 2007) and selection of the dominant follicle (DF) (Mihm and Austin, 2002), which can ovulate, become atretic, or develop into a cyst or non-ovulatory follicle (Savio et al, 1990a;Beam and Butler, 1997;Sakaguchi et al, 2006). Factors affecting the fate of DFs pp are closely related to the metabolic status of animals -for instance, prepartum diet (Cavestany et al, 2009), energy balance (EB) pp (Beam and Butler, 1997), but also parity (Zhang et al, 2010).…”
mentioning
confidence: 99%
“…It has been determined that the first follicular growth wave emerges soon after delivery and is independent of the EB of the animal (Butler, 2003). Selection of its DF (> 9 mm) takes place around day 10 pp (Savio et al, 1990a). DFs from the first follicular growth wave ovulate in 30-80% by day 20 (Crowe, 2008), and the interval from parturition to the first ovulation seems to be dependent on parity (Darwash et al, 1997;Tanaka et al, 2008).…”
mentioning
confidence: 99%